AN EMPIRICAL STUDY OF SOFTWARE ENGINEERING MODEL FOR SOFTWARE DEVELOPMENT - Jetson, V Rajiv; Prasad, Dr.G Satyanarayana (IJRDO -Journal of Computer Science Engineering, 2015)
Software worth billions and trillions of dollars have gone waste in the past due to lack of proper techniques used for developing software resulting into software crisis. Historically, the processes of software development have played an important role in the software engineering. A number of life cycle models have been developed in last three decades. This paper is an attempt to analyze the software process model by various documented standard model.